Developing Resilient Urban Waterfronts: Integrating Adaptation into Urban Development and Management. - Veelen, Peter C. van (Springer Fachmedien, 2017)
There is a growing attention for integrating climate change adaptation into policies, strategies and decision-making processes (e.g. mainstreaming). This paper explores to what extent climate adaptation can be integrated into processes of urban development and change, based on case study research in Rotterdam waterfront area (Feijenoord). In this research "adaptation opportunities" are identified, by mapping all planned spatial investments in brownfield development, urban renovation, and maintenance projects of public and private infrastructures and assets. These adaptation opportunities are seen as momentum for enhancing resilience at relatively low costs. The Feijenoord case shows that intervention opportunities, based on an assessment of life cycles and investment projects is not effective due to a lack of strategic asset management and because processes of urban development are becoming increasingly fragmented and uncertain. The paper concludes that it is more effective to focus on "intervention opportunities" that are based on an understanding of the economic and organisational processes of urban development and change.
Keywords: Hafenstadt; Küste; Ufer; Stadtteil; Bebauung; Resilienz; Transformation; Nachhaltigkeit; Stadtentwicklung; Anpassung; Klimawandel; Klimaanpassung; Intervention